The Responsiveness of Corporate Investments to Changes in Corporate Income Taxation During the Financial Crisis: Empirical Evidence from Slovenian Firms. Issue 9 (1st September 2016) - Črnigoj, Matjaž
ABSTRACT: I examine the responsiveness of corporate investments to changes in corporate income taxation during the financial crisis. When investigating tax effects in financially constrained firms, the model of investment demand needs to be extended to include an additional channel through which taxes could affect investments. I model the tax effects via two transmission channels, the traditional user cost of capital channel and the cash flow channel, which is crucial for financially constrained firms. The empirical results show that corporate investments in financially constrained firms do not respond to changes in corporate income taxation through the user cost of capital channel, but there is strong evidence of the effect that materializes through the cash flow channel.